The influence of student engagement and school well-being on student learning motivation - Gladis Corinna Marsha (Universitas Muhammadiyah Banjarmasin, 2024)
This study aims to examine the influence of student engagement and school well-being on learning motivation among students. The research respondents consisted of 95 students from the Faculty of Psychology at Universitas Muhammadiyah Banjarmasin, class of 2023 and 2024, who were selected using the simple random sampling technique. The estimated value of Cronbach's Alpha reliability on the student engagement scale is 0.907, on the school well-being scale is 0.908, and on the learning motivation scale is 0.929. The results of the analysis using multiple linear regression show that student engagement and school well-being simultaneously have a significant effect on learning motivation (R² = 0.339). Partially, student engagement has a significant influence with b = 0.64 (p < 0.001), and school well-being with b = 0.206 (p = 0.028). These results indicate that the higher the student’s engagement in learning and their school well-being in the educational environment, the greater their motivation to learn. This research emphasizes the importance of creating an academic environment that supports student engagement and school well-being to enhance students' learning motivation. Further studies are recommended to explore additional factors that influence learning motivation to expand the understanding of this dynamic.